THE COMPARISON OF PERSONAL TRAITS OF THE PROFESSIONAL AND AMATEUR MUSICIANS - Arshava, Iryna; Kutepova-Bredun, Victoria (European Scientific Journal, ESJ, 2015)
The existing research findings as to the differences in the personal structures of professional and amateur musicians are related mainly to the motivational aspects of the personality including social motives, selfexpression and self-achievement. The personality traits has less been studied. The objective of this paper is to demonstrate the differences between the professional and amateur musicians in global personality traits as well as the impact on their psychological well-being and adaptivity. On a sample of a 122 participants split into two non-equivalent sub-groups of professional and amateur musicians in quasi-experimental fashion differences between the global personality traits and their impact on the individuals` adaptivity and well-being were assessed with Mann-whitney U-test. Dispositional traits were assessed with four psychodiagnostic methods including Five-Factor Inventory (MacCrae&Costa), the Scales of Psychological Well-Being, Multi- Factory Personal Questionnaire Adaptivity and the Hospital Anxiety and Depression Scales. It has been found out that professional musicians differ from amateur in higher levels of neuroticism, anxiety, asthenic features and overall level of psychological well-being. It is worth while mentioning in particular that despite high level of neuroticism and anxiety the professional musicians enjoy an overall high level of psychological well-being which has signified the therapeutic and harmonizing role of musical activity on the human-being.